Incidencia del agregado grueso del río Huallaga en diseño de mezclas de concreto simple para cimentaciones corridas - Sánchez Mercado, Nestor Jesús (2000)
The construction in the Region San Martín is W1 problem amt to be resolved, which is aggravated by several factors including the main being the economic, for the high cost of investment needed to build a common dwelling of mto or more floors. The present thesis work provides the solution and the proper use of basic materials in bullfights foundations of housing construction. The quarry used for tests of the specimens is the quarry of Rosillo Santa, located at Km 63 Tarapoto, Juanjui road and cement to be used is cement Pacasmayo type l. Them trials is developed in the laboratory of technology of materials of the University national of Cajamarca and laboratories private, these trials consist of analysis particle size, design of mixtures, tests to the bending, compression and cutting.